Modulation of IRAK4 as a therapeutic strategy against monosodium urate- and xanthine-induced inflammation in macrophages and HepG2 cells - Umar, Sadiq; Chang, Huan T.; Maienschein-Cline, Mark; Ravindran, Sriram (Frontiers in Immunology, 2026)
BackgroundInterleukin-1 receptor-associated kinase 4 (IRAK4) is a pivotal mediator of Toll-like receptor (TLR) and interleukin-1 receptor (IL-1R) signaling, critically involved in innate immune activation and pro-inflammatory cytokine production. Dysregulated IRAK4 activity contributes to chronic inflammation in both immune and non-immune cells. In this study, we evaluated the immunomodulatory potential of a selective IRAK4 inhibitor on monosodium urate (MSU) crystal-stimulated macrophages and xanthine-challenged HepG2 cells to assess its therapeutic potential.MethodsHuman peripheral blood mononuclear cells (PBMCs) were pretreated with 1 µM IRAK4 inhibitor (IRAK4i) overnight, followed by stimulation with 100 µg/mL of MSU for either 30 min or 24 h. Conditioned medium was collected for ELISA and RNA for qPCR to quantify pro- and anti-inflammatory factors. Cell lysates were prepared to analyze various TLR/IL-1β signaling proteins, including phosphorylated IRAK4, P38, ERK, and JNK. Phagocytosis was assessed using a Vybrant™ phagocytosis assay kit in PBMCs. HepG2 cells were also utilized and pretreated with 1 µM of IRAK4i overnight, followed by stimulation with 2.5 mM of xanthine for 24 h to assess the expression of pro-inflammatory cytokines and xanthine oxidoreductase.ResultsPrimary macrophages and HepG2 cells were treated with a potent IRAK4 inhibitor in the presence and absence of MSU or xanthine. In macrophages, IRAK4 inhibition significantly reduced the expression of TNF-α, IL-6, and IL-1β at both mRNA and protein levels while promoting polarization toward an anti-inflammatory (M2-like) phenotype alongside reduced activation of the nuclear factor-κB (NF-κB) and MAPK pathways. In HepG2 cells, IRAK4 blockade attenuated xanthine-induced expression of xanthine dehydrogenase and pro-inflammatory cytokines.ConclusionThese findings demonstrate the dual anti-inflammatory effect of IRAK4 inhibition in both immune and hepatic cells and suggest a promising strategy to mitigate inflammation in gout.